ACCESS TO FOOD AND FOOD AND NUTRITION SECURITY: ASSESSMENT OF SITUATION IN MUNICIPALITIES IN BAHIA, BRAZIL - Laís Santos Calmon; Sandra Maria Chaves Santos; Marlus Henrique Queiroz Pereira (Demetra, 2016)
Objective: To evaluate the situation of food and nutrition security at the municipalities of Bahiastate and the main determinants in the dimension of access to food. Methods: We used a protocol of indicators that evaluates food and nutrition security covering four dimensions (availability, food access, food consumption and biological use of nutrients). Secondary data on Bahia municipalities (available in public online databases) were used. Prevalence measures were calculated and associations were verified between the variables of the study. Results: In the municipalities evaluated, it was noted that 119 municipalities (28.7%) were in light Food Insecurity and 286 (69.1%) were in moderate Food Insecurity. For the AccesstoFood  dimension, there was a predominance of moderate Food Insecurity (71.5%), and the indicators thatcontributed most to this situation  were the proportion of people with low income and percentage of population aged  15 years or more  and less than 4 years of schooling. There was a significant association between Food Insecurity in the municipalities, considering all dimensions and the status of Food Insecurity at the dimension of Access to Food (p<0.000), and between the situation of Food Insecurity at the dimension of Access to Food and the lowest Municipal Human Development Index (p<0.000). Conclusion: Although the dimension Access to Food was strongly related to Food Insecurity, it was not enough to explain it individually in Bahia municipalities. The protocol used can help managers to define strategical actions to face the problem.